Domestic Violence in The Perspective of Civil and Islamic Criminal Law - Saepullah, Usep; Hopipah, Eva Nur (Universitas Islam Negeri Raden Intan Lampung, 2023)
The cases of domestic violence in Indonesia tend to increase from time to time. Based on data released by the National Commission on Violence Against Women in 2020, the number of domestic violence complaints received was recorded at 4,371, an increase from 4,322 cases in the previous year. From the perspective of Islamic criminal law, domestic violence is classified as jarīmah takzīr (criminal acts where the legal provisions are left to the discretion of the authorities) whereas in positive law domestic violence is regulated in Law of the Republic of Indonesia Number 23 of 2004 concerning the Elimination of Domestic Violence. This research discusses domestic violence in Bandung and examines the methods for resolving cases at the Religious Courts and the Bandung Police. The aim is to find the characteristics and methods of resolving cases in the two institutions. This research is classified as field research using comparative methods. Data was obtained from the document available at the Bandung Religious Court and the Bandung City Police Station. This research finds that more domestic violence cases in Bandung City were resolved through criminal channels (police) rather than civil channels (Religious Courts). This research concludes that although both Islamic Law and Positive Law view domestic violence as a criminal act, there are differences in the methods of resolving them in the Religious Courts and Bandung Police. This is because the competence of each institution is different. The Religious Court only handles the civil side, while the Bandung Police handles the criminal side.